Absolute Lymphocyte Count as a Marker for Cytomegalovirus Infection After Heart Transplantation. Issue 3 (13th October 2022) - Schoeberl, Armin-Kai; Zuckermann, Andreas; Kaider, Alexandra; Aliabadi-Zuckermann, Arezu; Uyanik-Uenal, Keziban; Laufer, Guenther; Goekler, Johannes
Abstract : Background: Previous studies indicate an association between reduced absolute lymphocyte count (ALC) and cytomegalovirus (CMV) infection after solid organ transplantation and have therefore highlighted the potential of ALC as a simple tool to predict CMV infection in transplant patients. This study aimed to examine the utility of ALC as a valuable marker for CMV infection in heart transplant patients. Methods: Clinical information and ALC data of all adult patients who received orthotopic heart transplantation at the Medical University of Vienna between January 2004 and May 2019 were collected. We performed a multivariable Cox regression model that incorporates repeated measurements of ALC as a time-varying continuous factor in 2 ways, first as continuous logarithmic factor considering a 50% decrease of ALC levels and second as binary factor using a threshold of 610 cells/μL. Results: One hundred fifty-eight (39%) patients developed CMV infection over the course of 2 y. Patients with lymphopenia were shown to be at higher risk of developing CMV infection both in the continuous approach (HR [per 50% reduction] 1.29; confidence interval [CI], 1.09-1.53; P = 0.003) and the binary approach with a cutoff of 610 cells/μL (HR 1.74; CI, 1.20-2.51; P = 0.003). Conclusions: This study demonstrated a strong association between reduced ALC and the development of CMV infection after heart transplantation. ALC value monitoring could provide an additional tool to assess individualized CMV risk after solid organ transplantation. Abstract :